Geospatial Variability of Soil Properties of the Different Villages in Arajiline Block of Varanasi District of Uttar Pradesh - Maurya, Shivam Kumar; Bharteey, Prem Kumar; Singh, G. R.; Bahuguna, Ayush; Luthra, Nidhi; Pal, Sudhir; Pradhan, Surajyoti; Rai, Sumit (International Journal of Bio-resource and Stress Management, 2024)
The current study was conducted at the different villages of the Arajiline block of Varanasi district, Uttar Pradesh, India during November, 2022–June, 2023 to evaluate the variability of soil properties and nutrient indexof soils. The random sampling technique was used to collect 40 soil samples at different locations with the help of GPS at 0–15 cm depth. The collected soil samples were air-dried in shade at room temperature, passed through a 2 mm filter paper, and analyzed for different physico-chemical properties. The result revealed that the TS (range 8.2–81.3%), VFS (range 4.2–35.5%), Silt (range 10.1–54.2%), Clay (range 7.7–38.8%), BD (range 1.08–1.45 g cm-3), PD (range 2.04–2.33), Porosity (range 30.24–51.56%) pH (range 6.4-7.8), EC (range 0.1-0.3 dS m-1), OC (0.2-0.6%), and available N, P, K, S, Ca, and Mg varied from 130.12–260.30 kg ha-1, 14.2-23.2 kg ha-1, 145.0–240.0 kg ha-1, 7.5–17.6 kg ha-1, 3.8–8.2 cmol(P+)/kg, and 2.1-4.1 cmol(P+)/kg, respectively. The findings indicated that the studied soils were slightly acidic to moderately acidic and free from salinity hazards; 70% of the soil samples were low in organic carbon, 30% were medium in organic carbon, and 100% of the soil samples were low in available N and medium in available P, K, and S. 100% of soil samples were found to be sufficient in exchangeable Ca and Mg. The findings of this research could help in crop nutrient management, fertilizer recommendation, and decision-making for increasing agricultural production and farmer profitability.